A Study on Students’ Motivation in English learning at the eleventh grade of SMAN 1 AIRTIRIS - Amin, Azri; Gushendra, Rizky (Indonesian Journal of Integrated English Language Teaching, 2023)
When learning English students really need motivation, therefore this research focuses on the importance of motivation in English learning. This study also aims to investigate the motivation that exists in students when learning in English learning. The research method used is a descriptive method of quantitative analysis where data is analyzed using SPSS version 21 and Microsoft Excel. This research was conducted from November 9, 2022 to December 26, 2022. Data collection was carried out by giving students a questionnaire which aims to determine the level of students' motivation when learning English. Questionnaires were distributed to 71 students from grade seven as a sample. Determination of this sample is done by simple random sampling of 5 classes. The findings show that the level of students' motivation in english learning from is at a good level. Furthermore, the dominant aspect or indicator of students' perceptions of motivation in english learning for grade 7 at SMAN 1 Airtiris is indicator 2.